Analisis Program Peningkatan Nilai PPID - Bening Pekerti (UNISBA Press, 2023)
Abstract. This research was made as a report on the author's internship at PT Semen Indonesia regarding any work that the author has done, especially regarding company information disclosure and the PPID (Information and Documentation Management Officer) value improvement program. In addition, this report is also made to explain from the beginning the author entered the internship until it was finished, as well as what results the writer got from the internship. From the results of this report it can be concluded that information disclosure is very important for a company to become a company that is in line with GCG (Good Corporate Governance). From this apprenticeship program the author gets a lot of practical knowledge, not just theory so that it can increase the author's abilities. Abstrak. Penilitian ini di buat sebagai laporan magang penulis di PT Semen Indonesia mengenai pekerjaan apa saja yang sudah penulis lakukan, terutama mengenai keterbukaan informasi perusahaan dan program peningkatan nilai PPID (Pejabat Pengelola Informasi dan Dokumentasi). Selain itu laporan ini juga dibuat untuk menjelaskan dari awal penulis masuk magang sampai dengan selesai, serta hasil-hasil apa saja yang penulis dapatkan dari magang. Dari hasil laporan ini dapat disimpulkan bahwa keterbukaan informasi sangat penting bagi sebuah perusahaan agar menjadi perusaahaan yang sejalan dengan GCG (Good Corporate Governance). Dari program magang ini penulis mendapat banyak pengetahuan secara praktik bukan hanya teori saja sehingga dapat menambah kemampuan penulis.